Efektivitas Promosi Kesehatan dengan Metode Peer Education terhadap Pengetahuan dan Sikap Remaja Putri tentang Dampak Pernikahan Dini di SMPN 5 Cilegon - Indah Nurfazriah; Ayuni Hartati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Early marriage is a reproductive health problem that has a negative impact on adolescent survival. The limited knowledge of adolescents about reproductive health has an impact on a lack of attitude which results in adolescents committing deviant acts. Interventions to increase youth knowledge and attitudes about the impact of early marriage are urgently needed, one of which is peer education. The purpose of this study was to analyze the effectiveness of health promotion using the peer education method on the knowledge and attitudes of young women about the impact of early marriage. The design of this study was the Pre-Experimental Pretest-Posttest without Control Group. The sample in this study were 59 class VII girls using the accidental sampling technique. The results showed a p value of 0.000, so it could be concluded that peer education was effective in increasing the knowledge and attitudes of young women about the impact of early marriage. It is hoped that schools can cooperate with local health agencies in the form of counseling and health education.